A Review on the Application of Internet of Things in Tea Planting and Processing - JIANG Youcang, YING Jiaqi, AN Huimin, CHEN Yuan, HUANG Yiwen, LIU Jiashun, LIU Zhonghua, HUANG Jian’an (Shipin Kexue)
Science and technology are the key productive forces to promote the development of intelligent agriculture. The tea industry is a specialty industry in China’s agricultural field. The current status of this industry is characterized by varying scale and uneven development among tea enterprises. With the development of intelligent agriculture, in order to further explore a scientific path for the development of the tea industry, digital technology represented by big data, Internet of Things (IoT) and artificial intelligence has been applied to tea planting, processing, sale and traceability, which has promoted the intelligent development of the tea industry to a certain extent. This paper focuses on the application of IoT in tea planting and the processing of six kinds of tea and scented tea. Finally, the problems existing in the application of IoT in the tea industry are discussed, which provides a reference for the subsequent integration of IoT technologies into the tea industry.